2019
DOI: 10.12659/msm.919347
|View full text |Cite
|
Sign up to set email alerts
|

Itraconazole Alters the Stem Cell Characteristics of A549 and NCI-H460 Human Lung Cancer Cells by Suppressing Wnt Signaling

Abstract: BackgroundCancer stem cells (CSCs) behave as their malignant counterparts, but persist after treatment, and possess properties that allow them to interact with their environment. Itraconazole, an antifungal agent, also has a role in suppressing tumor progression, but its effects in regulating tumor cell stemness remain unclear. This study aimed to evaluate the effects of itraconazole on A549 and NCI-H460 human lung cancer cell stemness in vitro.Material/MethodsA549 and NCI-H460 human lung cancer cells and BEAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Additionally, itraconazole indeed could partially reverse the radiation resistance of NPC spheroids. Consistently, a recent work showed that itraconazole attenuates the stemness of lung cancer cells 21 . However, it is still unclear whether itraconazole holds the similar effects on other tumor cell stemness.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Additionally, itraconazole indeed could partially reverse the radiation resistance of NPC spheroids. Consistently, a recent work showed that itraconazole attenuates the stemness of lung cancer cells 21 . However, it is still unclear whether itraconazole holds the similar effects on other tumor cell stemness.…”
Section: Discussionmentioning
confidence: 64%
“…Consistently, a recent work showed that itraconazole attenuates the stemness of lung cancer cells. 21 However, it is still unclear whether itraconazole holds the similar effects on other tumor cell stemness. Notably, antifungal infection is an important implication during hematopoietic stem cell transplantation 27 and CSC shares the similar characteristics with the normal stem cells 28 ; thus, future work should be focused on whether itraconazole has the similar effects on normal stem cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To test whether the cellular and molecular effects observed for DEPs are specific for mGS cells, we used another type of cells, lung epithelial A549 cell line that have some characteristics of stem/progenitor cells [30]. We first examined their morphology following incubation with 1, 10, and 100 µg/mL DEPs.…”
Section: Effects Of Deps On A549 Lung Cellsmentioning
confidence: 99%